2018
DOI: 10.1103/physrevc.97.054318
|View full text |Cite
|
Sign up to set email alerts
|

Spin alignment following inelastic scattering of Ne17 , lifetime of F16 , and its constraint on the continuum coupling strength

Abstract: The sequential two-proton decay of the second excited state in 17 Ne, produced by inelastic excitation at intermediate energy, is studied. This state is found to be highly spin aligned, providing another example of a recently discovered alignment mechanism. The fortuitous condition that the second decay step is slightly more energetic than the first, permits the lifetime of the one-proton daughter, the ground-state of 16 F, to be determined from the magnitude of the final-state interactions between the protons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 36 publications
3
24
0
Order By: Relevance
“…Coulomb final-state interaction between the two protons resulted in a depletion of events near θ pp =0 compared to θ pp =180 • . From fitting the magnitude of this effect, the intrinsic width of 16 F g.s could be extracted and was found to be consistent with the value obtained from directly measuring the width of the peak line shape [24]. Here, the decay width of the two possible intermediate states are larger (62 and 47 keV) than the value of 23 keV for the 16 F g.s.…”
Section: Distributions Of Relative Angle Between Protonssupporting
confidence: 77%
See 2 more Smart Citations
“…Coulomb final-state interaction between the two protons resulted in a depletion of events near θ pp =0 compared to θ pp =180 • . From fitting the magnitude of this effect, the intrinsic width of 16 F g.s could be extracted and was found to be consistent with the value obtained from directly measuring the width of the peak line shape [24]. Here, the decay width of the two possible intermediate states are larger (62 and 47 keV) than the value of 23 keV for the 16 F g.s.…”
Section: Distributions Of Relative Angle Between Protonssupporting
confidence: 77%
“…To describe spectra of 14 O resonances and their properties, we used the Shell Model Embedded in the Continuum (SMEC) which describes resonances in the framework of the shell model for open quantum systems [1,2,5,25,26]. Recent SMEC applications included the study of correlations and clustering in near-threshold states [1][2][3][4] and the change of the continuum coupling strength for like and unlike nucleons in exotic nuclei [24].…”
Section: Theoretical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of inelastic scattering with fast beams have shown the possibility of achieving strong spin alignment if the target nucleus remains in its ground state after the inelastic scattering [1][2][3][4]. Figure 3 shows the distributions of target excitation energy deduced from the center of mass of the p+ 12 N and 2p+ 11 C events assuming two-body kinematics for inelastic scattering reactions.…”
Section: B Decay Angular Distributionsmentioning
confidence: 99%
“…The value of V 0 was constrained by the measured proton width of the 1/2 + 3 state. The spin-exchange parameter α has a value α = 2 which is appropriate for nuclei in the vicinity of driplines [13][14][15].…”
mentioning
confidence: 99%